On Daniel Solomon’s life-long work on ‘City of Love versus City of Hope’ (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2020)
Daniel Solomon’s Housing and the City. Love versus Hope “explores the successes and failures of cities such as San Francisco, Paris, and Rome in a century-long battle between the so-called ‘City of Hope’, which sought to replace traditional urban fabric with more rational housing patterns, and the City of Love – love of the city’s layered history and respect for its intricate social fabric”. A perfect statement to summarize the work of one of the co-founders of the “Congress for the New Urbanism” (1993) a movement, as reported on the CNU (Congress for the New Urbanism) official web site, “united around the belief that our physical environment has a direct impact on our chances for happy, prosperous lives. New Urbanists believe that well-designed cities, towns, neighborhoods, and public places help create community: healthy places for people and businesses to thrive and prosper”.